2019
DOI: 10.1016/j.jwpe.2019.100941
|View full text |Cite
|
Sign up to set email alerts
|

Microfiltration membrane processes: A review of research trends over the past decade

Abstract: Since its inception in the 19 th century, microfiltration (MF) has evolved as a membrane-based separation technology for treating various effluents and wastewaters. This review aims to familiarize its readers with general and specific research trends on various topics in MF. The level of research interest has been measured by the number of publications in that area for each year. An increasing research trend was observed from the number of publications since 2009 to 2018 with MF as the major topic. During the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(79 citation statements)
references
References 77 publications
1
67
0
4
Order By: Relevance
“…Therefore, better understanding of overall fouling is the prime objective to develop membrane processes and increase membrane flux [25,35]. Although MF research has gained immense importance over the past decade [41], based on literature review, studies focusing on the fouling importance during microfiltration of fermentation broths in cross-slow systems with ceramic membranes are very limited (Table A1).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, better understanding of overall fouling is the prime objective to develop membrane processes and increase membrane flux [25,35]. Although MF research has gained immense importance over the past decade [41], based on literature review, studies focusing on the fouling importance during microfiltration of fermentation broths in cross-slow systems with ceramic membranes are very limited (Table A1).…”
Section: Introductionmentioning
confidence: 99%
“…Ceramic filters are fabricated using alumina, zirconia or zeolite, materials that withstand extreme pH, pressure conditions and high flux rates [90]. These characteristics facilitate effective cleaning with acidic or alkali solutions, indicating ceramic membranes as ideal candidates for processing complex effluent streams of sludge nature [80]. They have gained widespread popularity due to their specific properties as they can withstand high temperatures which are applied for instance in membrane reactors in which they contain the catalytically active sites and function as separation barrier as well [91].…”
Section: Inorganic Membranesmentioning
confidence: 99%
“…A review of microfiltration (MF), conducted by Anis, Hashaikeh, and Hilal (2019), indicated that significant research was occurring in the areas of modeling, wastewater treatment, membrane fabrication, and membrane modification.…”
Section: Annual Literature Reviewmentioning
confidence: 99%